Integrating Multicultural Values into Islamic Religious Education: Strategies for Fostering Inclusive Character Development in Elementary Schools - Mappanyompa Mappanyompa (Universitas Muhammadiyah Mataram, 2026)
Abstract: This research is urgent given the growing need to foster inclusive character development among elementary school students amid social diversity and the dynamics of interaction in the digital age. However, a gap exists: while Islamic Religious Education (IRE) instruction has been implemented systematically, the internalization of multicultural values has not been consistently integrated into teaching practices and students’ daily lives. This study aims to analyze the integration of multicultural values in Islamic Religious Education (IRE) instruction to foster inclusive, tolerant, and harmonious attitudes. The approach used is descriptive qualitative, involving 25 fifth-grade students, 7 teachers, and 25 parents, through in-depth interviews, participant observation, and documentation analyzed using the Miles and Huberman model. The research findings demonstrate the integration of multicultural values through diversity-related materials, participatory methods (heterogeneous discussions, role-playing), and the exemplary behavior of inclusive teachers. The data findings indicate a decrease in verbal bullying and an increase in students’ empathy, tolerance, and cooperation. Recommendations for future research include the development of a digital model, expansion of the context, and the use of a comprehensive mixed-methods approach.Abstrak: Penelitian ini menjadi urgen seiring meningkatnya kebutuhan pembentukan karakter inklusif pada siswa sekolah dasar di tengah keberagaman sosial dan dinamika interaksi di era digital. Namun, terdapat kesenjangan ketika pembelajaran Pendidikan Agama Islam telah berjalan sistematis, sementara internalisasi nilai multikultural belum konsisten dalam praktik pembelajaran dan kehidupan siswa. Penelitian ini bertujuan menganalisis integrasi nilai multikultural dalam pembelajaran PAI guna membentuk sikap inklusif, toleran, dan harmonis. Pendekatan yang digunakan adalah kualitatif deskriptif dengan subjek 25 siswa kelas V, 7 guru, dan 25 orang tua, melalui teknik wawancara mendalam, observasi partisipatif, dan dokumentasi yang dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan integrasi nilai multikultural melalui materi keberagaman, metode partisipatif (diskusi heterogen, role play), dan keteladanan guru inklusif. Temuan data mengindikasikan penurunan bullying verbal serta peningkatan empati, toleransi, dan kerja sama siswa. Rekomendasi penelitian selanjutnya meliputi pengembangan model digital, perluasan konteks, dan penggunaan pendekatan mixed method komprehensif.